The Contributions of Geographic Information Systems (GIS) to the Creditability and Transparency of the 2016 General Elections in Ghana (Global Journal of Human-Social Science, 2018)
An election is one of the most important human institutions as its outcomes may have diverse effects on the people and the nation as a whole. Election offers people the opportunity to select a leader or set of leaders who would oversee the affairs of the people, their communities and the nation at large for a period. Peaceful elections have contributed to the democratic and stable atmospheres in most countries. Election involves a lot of processes such the casting of votes, counting of the vote cast, displaying of results in figures and numbers and declaring of the winner for the poll. Each of these processes is crucial to the creditability and transparency of the election, but displaying, and the representation of election result are more crucial since figures and numbers can be manipulated easily by the electoral commission. One may argue that this problem of electoral data representation can be solved statistically by using graphs and bar chart or pie chart, but the locations of the electoral colleges would be statistically very hard to fix. An alternative approach to electoral data representation is through the use of Geographic Information Systems (GIS). Geographic Information Systems can display election results visually and represent the locations where these election results were being obtained.